قناعات معلمي العلوم لتوظيف التقييم البديل في إكساب طلبة المرحلة الأساسية لمهارات العمل المخبري - عبيدو، مانيا عبدالعزيز عبدالمنعم; البركات، علي أحمد (الجامعة الإسلامية بغزة - شئون البحث العلمي والدراسات العليا, 2017)
سعت الدراسة الحالية إلى تقصي درجة قناعة معلمي العلوم للمرحلة الأساسية لتوظيف التقييم البديل في إكساب طلبتهم لمهارات العمل المخبري. ولتحقيق ذلك. قام الباحثان بإعداد أداتي الدراسة بعد أن تم التأكد من صدقهما وثباتهما. وتكونت عينة الدراسة من 146 معلما ومعلمة، تم اختيارهم عشوائيا للاستجابة علي الاستبانة. بالإضافة إلي 27 معلما ومعلمة تم اختيارهم بطريقة متيسرة لغرض المقابلة شبه المقننة. وأظهرت نتائج الدراسة أن أفراد الدراسة لديهم قناعات عالية لتوظيف التقييم البديل في إكساب الطلبة مهارات العمل المخبري. كما بينت النتائج عدم وجود فروق دالة إحصائيا في استجابات أفراد الدراسة تعزى إلى جنسهم ومؤهلاتهم العلمية وخبراتهم التدريسية. وعلاوة على ذلك كشفت نتائج الدراسة المستمدة من المقابلات شبه المقننة أن أفراد الدراسة اكدرا أن التقييم البديل يقدم صورة شاملة لتحصيل الطلبة. فضلا عن تقديم مؤشرات حقيقية تظهر معارف الطلبة. وكفاياتهم. وقدراتهم التي تم تشكيلها في المواقف التعليمية التعلمية. كما بينت نتائج المقابلة أن لدى أفراد الدراسة قناعات تامة بان لتقييم البديل دور حاسم في إكساب الطلبة مهارات العمل المخبري بشكل افصل عن أشكال التقييم التقليدي. وبناء علي ذلك، خلصت الدراسة إلى مجموعة من التوصيات ذات الصلة.
The present study aimed at investigating the degree of primary science teachers' convictions of using the alternative assessment in primary stage pupils' acquisition of laboratory work skills. To achieve the objective of the study, the researchers prepared the study instruments after making sure of their validity and reliability. The instruments consisted of questionnaire, and a semi-structured interview. The sample of the questionnaire consisted of (146) male and female primary science teachers, who were randomly chosen. In addition, an available sample consisted of 27 participants, which was selected to conduct interviews. The findings of the study showed that the degree of primary science teachers' convictions of using the alternative assessment in primary stage pupils' acquisition of laboratory work skills achieved higher averages. Moreover, it was found that there were no significant differences in the participants' respondents attribute to their gender, academic qualifications, and instructional experience. In addition, the findings of the semi-structured interview revealed that a alternative assessment provides more comprehensive insight into students’ achievements and gives authentic indicators with respect to pupils' knowledge, abilities, skills, attitudes, and competences which are constructed during the course teaching and learning settings. Based on these findings, we can say that teachers' convictions reflect the crucial role of alternative assessment in science learning environments rather than traditional forms of laboratory work assessment. Based on this, a set of virtual recommendations has been introduced to the Jordanian Ministry of Education.
Keywords: التقييم البديل -- مادة العلوم -- معلمو العلوم -- مهارات العمل المخبري -- طلبة المرحلة الأساسية